AGRIBUSINESS RISK OF DAIRY FARMER COOPERATIVE (CASE STUDY: BOGOR DAIRY PRODUCTION AND LIVESTOCK BUSINESS COOPERATIVE) - Nurunisa, Venty Fitriany; Fadila, Ila (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
KPS-Bogor is one of the largest dairy cooperatives in Indonesia. The cooperativeconsists of 127 active farmers, produces an average of 78.8 liters of milk/person/day. However, the quantity and quality of milk produced is very volatile which causes fluctuations in the income of dairy farmers. Considered the role of cooperative to agricultural development, and its unique nature, risk analysis research is an interesting yet rarely conducted. Therefore, the objectives of this study are to analyze the agribusiness risks faced by the KPS-Bogor, and to analyze risk priorities faced by the KPS-Bogor. This research is a qualitative research, using Failure Mode Effect Analysis (FMEA) and Fishbone Diagram. The study results show that the cooperative faces 6 sources of risk that have the potential to cause losses , namely production risk (bacteria and the absence of SOPs for farming method), market risk (Dairy Processing Industry’s (DPI) market structure), financial risk (delayed payment of its member’s debt), legal risk (GMP standardization is not yet implemented), and human resource risk (low commitment of the workers). FMEA and Fishbone Diagram show that the low commitment of the workers, the absence of farming SOP, and the DPI market structure are the most risky sources which have highest level of severity, occurrence and detection that can cause losses to KPS-Bogor. Unussualy, this research found human resource risk valued higher than the production risk factor, which mainly become the main risk source in agricultural business.